Thoracoscopic Intercostal Nerve Block with Cocktail Analgesics for Pain Control After Video-Assisted Thoracoscopic Surgery: A Prospective Cohort Study - Li J; Dong Y; Guo J; Wang L; Tian J; Wang L; Che G (Journal of Pain Research, 2024)
Jue Li,1– 3,* Yingxian Dong,1– 3,* Jiawei Guo,4 Lei Wang,1 Jie Tian,1– 3 Li Wang,4 Guowei Che1– 3 1Department of Thoracic Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Lung Cancer Center, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3West China Clinical Medical College, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 4The Third Affiliated Hospital of Xinxiang Medical University, Xinxiang, Henan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guowei Che, Department of Thoracic Surgery, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China, Tel/Fax +86-28-86298113, Email cheguoweixw@126.comObjective: To evaluate whether using a cocktail of intercostal nerve blocks (TINB) during thoracoscopic surgery results in better clinical outcomes than patient-controlled analgesia (PCIA).Methods: Patients in two medical groups undergoing video-assisted thoracoscopic surgery (VATS) for pulmonary nodules in West China Hospital of Sichuan University were collected consecutively between March 2022 and December 2022. The groups were divided into two subgroups based on their analgesic program, which were TINB group and PCIA group. The primary outcome was the visual analogue scale (VAS) of the two groups at different stage after surgery and after discharge. Any analgesic related adverse events (ARAEs) were also recorded.Results: A total of 230 patients who underwent VATS were enrolled, in which 113 patients (49.1%) received a cocktail TINB after surgery, and 117 patients (50.9%) received a PCIA. After PSM, 62 patients in each group were selected. The difference of resting VAS (RVAS) and active VAS (AVAS) at different stage during hospitalization was only related to the change of period (p < 0.05, p < 0.05), and the two groups showed no significant differences in RVAS or AVAS during hospitalization (p = 0.271, p = 0.915). However, the rates of dizziness (4.84% vs 25.81%, p = 0.002), nausea and vomiting (0 vs 22.58%, p < 0.05), fatigue (14.52% vs 34.87%, p = 0.012), and insomnia (0 vs 58.06%, p < 0.05) in TINB group were lower than that in PCIA group. Besides, AVAS and RVAS at 7, 14, and 30 days after discharge in TINB group were both significantly lower than that in PCIA group (p < 0.05, p < 0.05).Conclusion: Cocktail TINB provided better analgesia after discharge and reduced the incidence of ARAEs in patients undergoing VATS. Keywords: analgesia, thoracoscopic intercostal nerve block, cocktail analgesia, video-assisted thoracoscopic surgery